Economic evaluation and health care rationing in Jordan: a study of national-level priority setting - Lafi, R.; Robinson, Suzanne; Williams, I. (2012)
Objectives: To explore the extent of and barriers to the use of economic evaluation in compiling the Jordan Rational Drug List in the health care system of Jordan. Methods: The research reported in this article involved a case study of the Jordan Rational Drug List. Data collection methods included semi-structured interviews with decision makers and analysis of secondary documentary sources. The case study was supplemented by additional interviews with a small number of Jordanian academics involved in the production of economic evaluation. Results: The research found that there was no formal requirement for cost-effectiveness information submitted as part of the decision-making process for the inclusion of new technologies on the Jordan Rational Drug List. Both decision makers and academics suggested that economic evidence was not influential in formulary decisions. This is unusual for national formulary bodies. The study identified a number of barriers that prevent substantive and routine use of economic evaluation. While some of these echo findings of previous studies, others—notably the extent to which the sectional interests of clinical groups and commercial (pharmaceutical) industry exert undue influence over decision making—more obviously result from the specific Jordanian context. Conclusions: Economic evaluation was not found to be influential in the Jordan Rational Drug List. Recommendations for improvement include enhancing capacity in relation to generating, accessing, and/or applying health economic analysis to priority setting decisions. There is a further need to incentivize the use of economic evaluation, and this requires that organizational and structural impediments be removed.